Introducing Bonsai Thinking: The Science of Learning, Unlearning, and Relearning for the Age of Continuous Adaptation - Oleksandra Halchenko (WISE Pendidikan Indonesia, 2025)
This study introduces the science of learning, unlearning, and relearning to explore the processes of learning, unlearning, and relearning within organisational contexts, offering a novel conceptual framework of bonsai thinking. The framework emphasises the cyclical nature of these processes, integrating cognitive, affective, and conative dimensions to foster continuous organisational development. This paper applies the System Test to investigate the three system archetypes that build and evaluate my definition of a learning-unlearning-relearning cycle – bonsai thinking. Using a metaphorical approach for theory-building, I introduce a discipline of bonsai thinking through its purpose, which implies that everything in nature is never complete (life-long learning), the need for creating meaningful controlled environments (life-wide learning), and as the art of bonsai involves shaping and training a tree to achieve a specific aesthetic, the art of learning to achieve a specific purpose (as I propose calling it life-deep learning). Through its elements, I suggest a new definition of a learning cycle: pruning for unlearning, wiring and positioning for relearning, and then watering and fertilising for learning. And through the interconnections, I base my approach to learning, unlearning, and relearning on the Trilogy of Mind — cognition, affection, conation, and on what I call the Trilogy of Education — neuroscience, happiness studies, and future studies to highlight the interconnectedness of thinking, feeling, and acting and offer a holistic approach to organisational learning. This study further discusses the practical implications of the framework for organisational development and highlights the need for future empirical research to validate the proposed model. The contribution of this research lies in introducing a novel 3D approach to organisational learning that integrates all three dimensions of human engagement, offering new insights into how organisations can effectively navigate continuous change and foster long-term growth.